Longitudinal Analysis Casts Doubt on the Presence of Genetic Anticipation in Heritable Pulmonary Arterial Hypertension - Larkin, Emma K. (American Thoracic Society, 2012)
Rationale: Analysis of the age of onset in heritable pulmonary arterial hypertension (HPAH) has led to the hypothesis that genetic anticipation causes younger age of onset and death in subsequent generations. With accrual of pedigree data over multiple decades, we retested this hypothesis using analyses that eliminate the truncation of data that exists with shorter duration of follow-up. Objectives: To analyze the pedigrees of families with mutations in bone morphogenetic protein receptor type 2 (BMPR2), afflicted in two or more generations with HPAH, eliminating time truncation bias by including families for whom we have at least 57 years of data. Methods: We analyzed 355 individuals with BMPR2 mutations from 53 families in the Vanderbilt Pulmonary Hypertension Registry. We compared age at diagnosis or death in affected individuals (n = 249) by generation within families with multigenerational disease. We performed linear mixed effects models and we limited time-truncation bias by restricting date of birth to before 1955. This allowed for 57 years of follow-up (1955–2012) for mutation carriers to develop disease. We also conducted Kaplan-Meier analysis to include currently unaffected mutation carriers (n = 106). Measurements and Main Results: Differences in age at diagnosis by generation were found in a biased analysis that included all birth years to the present, but this finding was eliminated when the 57-year observation limit was imposed. By Kaplan-Meier analysis, inclusion of currently unaffected mutation carriers strengthens the observation that bias of ascertainment exists when recent generations are included. Conclusions: Genetic anticipation is likely an artifact of incomplete time of observation of kindreds with HPAH due to BMPR2 mutations.